Safety assessment of the process Coca‐Cola HBC, based on the NGR technology, used to recycle post‐consumer PET into food contact materials - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Andrew Chesson; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal)
Abstract The EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) assessed the safety of the recycling process Coca‐Cola HBC (EU register number RECYC285), which uses the NGR technology. The input is washed and dried poly(ethylene terephthalate) (PET) flakes mainly originating from collected post‐consumer PET containers, with no more than 5% PET from non‐food consumer applications. The flakes are dried (step 2), melted in an extruder (step 3) and decontaminated during a melt‐state polycondensation step ■■■■■ (step 4). In step 5, the material is granulated. Having examined the challenge test provided, the Panel concluded that the melt‐state polycondensation (step 4) is critical in determining the decontamination efficiency of the process. The operating parameters to control the performance of the critical step are the pressure, the temperature, the residence time (depending on the mass and throughput of the melt) and the characteristics of the reactor. It was demonstrated that this recycling process is able to ensure that the level of migration of potential unknown contaminants into food is below the conservatively modelled migration of 0.1 μg/kg food. Therefore, the Panel concluded that the recycled PET obtained from this process is not of safety concern when used at up to 100% for the manufacture of materials and articles for contact with all types of foodstuffs, including drinking water, for long‐term storage at room temperature, with or without hotfill. The final articles made of this recycled PET are not intended to be used in microwave and conventional ovens and such uses are not covered by this evaluation.